Faculty of system computer and software engineering asset management using RFID - Faidzarizal, Idris (2012)
Nowadays,many application system use online system and software to interact with the user.It is because online system has many advantages rather than using manual system.Asset management using RFID(Radio Frequency Identification) is very important to organization.System is an example of asset system that will be develop for lab administrators to manage all device in the labs.In this project system using RFID,several modules will be applied to the lab management system.All these modules are choosing based on the lab administrator and user request.This project has its objectives and problem statements that give the reason why this asset management system should be develop. Before developing the project,the developers should make a plan that consist the objectives,problem statements, scopes,and methodology including the system analysis, system design and system requirement that will used.All these components will helps the developers what should they develops and how to develops the system.Asset management is produce an easy platform for both new student and faculty administrator in registration process.